A psychiatric service at a community hospital - Ashley-Smith, Andrew (Department of Psychiatry and Mental Health, 2017)
The purpose of this dissertation is to evaluate an attempt to use the facilities of a general hospital with minimal psychiatric cover to deal with acute psychiatric conditions. This is in keeping with current psychiatric opinion in South Africa as expressed by Dr. C.W. Allwood and Dr G.A.D. Hart. This dissertation will examine the needs structure, difficulties and results of the provision of a service dealing with acute psychiatric disorders in a peripheral General Hospital and make suqqestions should similar satellite facilities be established at other peripheral hospitals. Although in principle. the concept of part-time specialist cover at a peripheral general hospital is not new in medical. surgical and gynaecological departments. the previous involvement of private psychiatrists within the teaching department has been in the form of out-patient department sessions only at academic and state psychiatric hospitals as is practiced in Cape Town. This project however allowed for the evaluation of emergency cases with subsequent referral to appropriate treatment centres if needed from a peripheral hospital. A consultation-liaison service within the general wards and the opportunity to conduct seminars, lectures and in-house training for all level of professional staff were also encompassed.